Любовь и выборы: [роман] / Лана Барсукова - Барсукова Лана (Экcмо, 2021)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58479 / Цена: 330.55 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Б 26 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44